Irreversible coma. Ethical considerations, forensic, clinical, electroencephalographic and neuropathological on 78 cases seen in a general hospital - Jerí, F. Raúl (1969)
Based on 78 cases of irreversible coma, studied clinical, electroencephalographic and neuropathologically, you come to a new definition of death. Ethical, forensic, clinical and therapeutic features of this conceptual innovation on one of the basic problems of medical practice implications are discussed.